"Joye without ending": Paul Bush’s The Extripacion of Ignorancy : An Early Case for Caesaropapism - Chibi, Andrew A. (Renaissance and reformation, 2022)
Paul Bush’s poem, The Extripacion of Ignorancy (1526), is a little known or regarded work that mixes Chaucer’s poetic tradition, orthodox theology, and obedience polemic into an advisory piece with Christian social ethics at the heart of a caesaropapism argument at least three years prior to Tyndale’s much more famous Obedience of a Christian Man. In rhyme royal, Bush explored sacred history, Scripture, and literary references to counter the harm of the Amicable Grant tax revolts and explore the value of a Crown-dominated system based on 1 Peter 2:17. By so doing, he sought to disseminate the ways and means of solving contemporary socio-political and religious tensions. The suggestion here is that Bush anticipated the arguments of the Tudor obedience polemicists of the 1530s. This article is an evaluation of the poem as a work of poetry, theology, and obedience polemic.